2020
DOI: 10.5435/jaaosglobal-d-20-00133
|View full text |Cite
|
Sign up to set email alerts
|

Current Variation in Joint Aspiration Practice for the Evaluation of Pediatric Septic Arthritis

Abstract: Introduction: Pediatric septic arthritis (SA) is a condition that can be associated with significant morbidity. Although previous research has been on predictive care pathways, scrutiny of the literature continues to reveal wide differences in the patient evaluation and management. The purpose of this study was to define the differences in joint aspiration for the evaluation of pediatric SA across pediatric tertiary care institutions in the United States. Methods: Surgeons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Among 355 children categorized as primary septic arthritis, 87 were excluded: contiguous osteomyelitis (23); JIA (12); penetrating inoculation (9); transient synovitis or viral reactive arthritis (8); other inflammatory arthritis (8); PSRA (3); systemic lupus erythematosus (3); postsurgical infection (3); immunocompromised (3); other adjacent infections not involving bone (3); disseminated gonococcal illness (2); and unknown due to insufficient documentation to determine a specific etiology (10). The remaining 268 children with primary septic arthritis were divided into confirmed (n = 134) and presumed (n = 134) cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among 355 children categorized as primary septic arthritis, 87 were excluded: contiguous osteomyelitis (23); JIA (12); penetrating inoculation (9); transient synovitis or viral reactive arthritis (8); other inflammatory arthritis (8); PSRA (3); systemic lupus erythematosus (3); postsurgical infection (3); immunocompromised (3); other adjacent infections not involving bone (3); disseminated gonococcal illness (2); and unknown due to insufficient documentation to determine a specific etiology (10). The remaining 268 children with primary septic arthritis were divided into confirmed (n = 134) and presumed (n = 134) cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4]8,11 The CORTICES group surveyed Principal Investigators from 18 Tertiary Pediatric Medical Centers and found significant differences in workflows and timelines of aspiration and intervention for septic arthritis. 8 High rates of culture-negative cases, similar appearance to inflammatory and reactive conditions and potential presence of unrecognized contiguous osteomyelitis pose obstacles to the exclusive study of primary septic arthritis. [1][2][3][4][5][6][7][8][9][10][11][12][18][19][20] As such, it is evident that there is a need for a more rigorous and systematic approach to evaluate, and treat primary septic arthritis in children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations